Telaah Kurikulum Terhadap Pergeseran Pendekatan Pembelajaran dalam Kurikulum Merdeka di Sekolah Dasar - Fathiah Nurul Rahmah; Dohar Lamhot Sitorus; Juanfan Rajagukguk; Agum Budianto (INDO PUBLISHING, 2026)
The Merdeka Curriculum is an educational policy designed to improve the quality of learning through a more flexible and student-centered approach. This article aims to examine the shift in learning approaches that has occurred in the implementation of the Merdeka Curriculum at the elementary school level. The study employed a literature review method with a qualitative descriptive approach. Data were collected from various scientific sources, including national journals, books, and policy documents relevant to the research topic. Data analysis was conducted using content analysis techniques to identify changes occurring in the learning process. The findings indicate that the Merdeka Curriculum encourages a shift from teacher-centered learning to student-centered learning. This shift is characterized by the implementation of differentiated learning, project-based learning, contextual learning, changes in the teacher's role as a facilitator, and the use of assessment that focuses more on the learning process. Although its implementation still faces several challenges, such as teacher readiness and limited supporting facilities, the Merdeka Curriculum has significant potential to improve the quality of learning in elementary schools. Therefore, collaboration among various stakeholders is necessary to support the successful implementation of the curriculum